Kajian Kecacatan Kerja Seni Bina pada Rumah Kondominium di Johor Bahru, Johor - Faizal, Mohamad Redzuan; Sarpin, Norliana; Masrom, Md Asrul Nasid; Khalid, Zailawati; Ismayatim, Norddin (Research in Management of Technology and Business, 2023)
The pace of development, especially in high-cost housing construction projects, is actively developing in Malaysia, and the production of a quality building is becoming more and more pressing. Several buyers and users of condominium houses state that there are defects and damage to their houses despite the high price that they pay for the houses. Therefore, this study was conducted to identify the types of architectural defects that occur, identify the factors that affect the architectural defects that occur as well as improvement measures to minimize the architectural defects that occur in condominium houses. This study was conducted using a quantitative method, which is the distribution of questionnaires to respondents. The respondents involved in this study are condominium housing developers in the Johor Bahru district. A total of 25 developer companies representing 89% of the response rate were involved in this study. The questionnaire was distributed using the online method via email and WhatsApp application. The data obtained was analyzed using a frequency analysis with the help of SPSS software. The results of this study found that the three main types of architectural defects that occur are damage to external walls, internal walls, and floors. In addition, the main factor affecting the defects of architectural work is the lack of skilled labor. While the improvement measures to minimize architectural defects that occur in condominium houses is to choose contractors who are experienced in architectural work and make periodic monitoring of contractors and subcontractors while they are doing work. This study is expected to help developers to further improve the quality of their construction to achieve the quality standards of high-cost condominiums expected by home buyers.